OUTCOMES OF LEARNING MATHEMATICS MATERIAL USING THE SAVI APPROACH (SOMATIC, AUDITORY, VISUAL, INTELLECTUAL) IN PRIMARY SCHOOL - Marisa, Riandi; Hayati, Rahmi (Kadikma, 2023)
This research was motivated by the problem of learning mathematics in simple fractions. The approach is a qualitative approach with the type of research being classroom action research. The data in this research is based on test results, observations and interview results. The data source in this research was class III UPTD students at SD Negeri 4 Peusangan, totaling 17 students with various levels of ability. Based on the research results, it was found that the SAVI approach was used for class III students at UPTD SD Negeri 4 Peusangan on simple fraction material. This is proven by the increase in the number of students who completed their learning in the initial test, namely from 47% belonging to the poor category before learning took place, in cycle I it increased to 65% belonging to the sufficient category and in cycle II it increased to 88% belonging to the good category. Meanwhile, the results of observations on the activities of teachers and students of class III UPTD SD Negeri 4 Peusangan on simple fractions material have increased with the percentage of teacher activity in cycle I, namely 85% belonging to the good category.